The Existence of Saung Angklung Udjo from a Macro Perspective: Strengthening Sundanese Culture Amid the Tide of Modernization - Aqila Nurlaily; Beby Rabiul Al Zahra; Gloria Gabriella; Muhamad Nazril; Nabhan Fajrul Falah; Naysilla Desti Aulia; Yusuf Firmansyah (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study analyzes the existence of Saung Angklung Udjo from a macro perspective and its role in strengthening Sundanese culture amid the challenges of modernization. The growing influence of globalization has created pressures on the sustainability of local cultural identities, making adaptive preservation strategies increasingly important. This study employed a qualitative descriptive approach using a literature review design based on scholarly publications related to Sundanese culture, angklung, cultural preservation, tourism, and globalization. The findings indicate that Saung Angklung Udjo functions as a cultural preservation center, an educational institution, a cultural tourism destination, and a medium of cultural diplomacy. Its contribution to strengthening Sundanese culture is reflected in the transmission of local values through artistic regeneration, participatory cultural education, and the promotion of the principles of silih asah, silih asih, and silih asuh. The institution has also maintained its relevance through performance innovation, digital engagement, educational tourism, and international collaboration. These strategies demonstrate that Saung Angklung Udjo serves as an adaptive and sustainable model for preserving local culture while responding to contemporary social change.